Addressing malnutrition in Nigeria: a narrative review of causes, impacts, and pathways to nutritional resilience - Jumoke Ilo; Olariike Kayode; Taiwo Jacob; Boluwatife Oduntan; Rukayat Lawal (Journal of Research in Applied and Basic Medical Sciences)
Background & Aims: Malnutrition remains one of the most pressing public health challenges in Africa, disproportionately affecting women and children. This dual burden of malnutrition, undernutrition, characterized by stunting, wasting, and micronutrient deficiencies, alongside overnutrition and its associated non-communicable diseases, compromises health and economic stability, particularly in sub-Saharan Africa. In Nigeria, malnutrition contributes to over 33% of under-five deaths annually, with stunting rates exceeding 50% in northern geopolitical zones. Materials & Methods: This study utilizes a narrative review approach to explore the underlying causes of malnutrition, including food insecurity, climate change, health challenges, poverty, and cultural practices, while also assessing intervention strategies. Results: Nearly 45% of Nigeria’s population experiences food insecurity, with rural communities disproportionately affected. Economic instability, conflicts, and environmental challenges in many parts of Nigeria further perpetuate cycles of poverty and food insecurity. Findings underscore the urgent need for climate-responsive policies, integrated disease prevention, and maternal education to mitigate the multifaceted impact of malnutrition. The study advocates for localized approaches to achieve long-term nutritional resilience. Conclusion: Malnutrition in Nigeria is a complex, multidimensional issue requiring urgent attention. Sustainable solutions must be driven by local resources, knowledge, and innovation.